2019
DOI: 10.1097/grf.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Updates and Controversies of Robotic-Assisted Surgery in Gynecologic Surgery

Abstract: minimally invasive surgery (MIS) is the standard approach to performance of several gynecologic procedures, including hysterectomy, gynecologic cancer staging procedures, myomectomy, pelvic organ prolapse repair, and select adnexal procedures. Robotic-assisted surgery, a computer-based MIS approach, has been adopted widely in the United States and several other countries. Robotics may offer technological and ergonomic benefits that overcome limitations associated with conventional laparoscopy; however, it is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 85 publications
0
38
1
7
Order By: Relevance
“…Chen et al [19] reported a steep decrease in docking time and console time in the robotic single-site hysterectomy group given chronological change. Although no study has addressed RM's learning curve, we assume it is similar to robotic hysterectomy [20]. Therefore, we assumed 24 cases within 1 year could master the technique needed for RM.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [19] reported a steep decrease in docking time and console time in the robotic single-site hysterectomy group given chronological change. Although no study has addressed RM's learning curve, we assume it is similar to robotic hysterectomy [20]. Therefore, we assumed 24 cases within 1 year could master the technique needed for RM.…”
Section: Discussionmentioning
confidence: 99%
“…These new ultrasound technologies could enable the development of personalised mesh design based on a CAD generated from these images, thereby taking 3D printing technologies to the next level of sophistication. Computer-assisted robotic surgery [ 163 , 164 ] is already becoming a routine surgical method due to its precision and minimal invasiveness. In future, we envision a personalised mesh, designed using a computer interface integrated with a pelvic ultrasound, that can be implanted using computer-assisted robotic surgery.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the high cost of RALM is a major disadvantage [ 4 , 5 , 6 , 7 , 8 ]. Varghese et al [ 9 ] reported the effectiveness and costs of hysterectomy: the cost of robotic hysterectomies was 1.5–3 times higher than the costs of conventional techniques, including laparoscopic or vaginal approaches [ 9 ]. Tapper et al [ 10 ] also showed that the cost of RALM was consistently higher than the cost of abdominal myomectomy or laparoscopic myomectomy, unless the robotic disposable equipment costs were less than $1400.…”
Section: Introductionmentioning
confidence: 99%